A Novel Integrated Active Herbal Formulation Ameliorates Dry Eye Syndrome by Inhibiting Inflammation and Oxidative Stress and Enhancing Glycosylated Phosphoproteins in Rats - Muz, Omer Ersin; Orhan, Cemal; Erten, Fusun; Tuzcu, Mehmet; Ozercan, Ibrahim Hanifi; Singh, Prafull; Şahin, Kazım (Mdpi, 2020)
Dry eye syndrome (DES) is a chronic condition of the eye with insufficient production of tears leading to inadequate lubrication of eyes. Symptoms of DES are associated with discomfort and redness of the eye, blurred vision, and tear film instability which leads to the damaged ocular surface. Inflammation and oxidative stress play a significant role in the pathogenesis of the disease. In this study, the protective effect of different doses (100 or 200 mg/kg) of a novel multi-component oral formulation of lutein/zeaxanthin, curcumin, and vitamin D3 (LCD) was evaluated using a rat model with benzalkonium chloride (BAC)-induced dry eye syndrome. The formulation was administered orally to rats for 4 weeks. We observed a significant improvement in tear volume, tear breakup time, tear film integrity, and reduction in overall inflammation in rats fed with the LCD at dose 200 mg/kg performing better than 100 mg/kg. Furthermore, the formulation helped in lowering oxidative stress by increasing antioxidant levels and restored protective tear protein levels including MUC1, MUC4, and MUC5AC with 200 mg of LCD having the most significant effect. The results strongly suggest that the combination of lutein/zeaxanthin, curcumin, and vitamin-D3 is effective in alleviating the symptoms of dry eye condition with a multi-modal mechanism of action.
Keywords: inflammation; oxidative stress; lutein; curcumin; vitamin D3; dry eye syndrome